“Land-Minds” and “Soft Human Paws:” Animals in the Poetry of Derek Mahon - Beatrice Orlandini (Caliban: French Journal of English Studies)
In this analysis of the Northern Irish poet Derek Mahon’s production, I will try to show how his poems convey the fundamental assumption that humans and animals are reciprocally sensitive to the encounter with the other, that there is a relationship of mutual implication and dependence between them. I will also try to show how this relationship has nonetheless ambivalent connotations in Mahon’s poems, for it holds both the possibility of misunderstanding and mutual fear, and of leading to a space if not of reconciliation, of a closer, however problematized, interaction, never excluding one or the other, but striving to acknowledge and celebrate this relationship’s ambiguous and at the same time rich complexity.